Produção recombinante de proteínas de fusão de SARS-CoV-2 para fins de diagnóstico e imunização - Astolfi, Bianca Soares (2023)
In the current COVID-19 scenario, there is still a demand for more effective diagnostic methods and improved immunization strategies. So far, the Receptor Binding Domain (RBD) of the Spike protein (S) has been the focus of diagnostic and immunization approaches. However, the Spike protein is susceptible to mutations, which can compromise current control strategies. In this context, this study aimed to produce recombinant fusion proteins of SARS-CoV-2, containing gene fragments and epitopes from the Envelope (E) and Membrane (M) proteins, fused to the RBD. These proteins were designed to be immunogenic and potentially useful in diagnostic and immunization platforms. The production process involved cloning the coding sequences and expression in Escherichia coli Rosetta (DE3). Although the expression was insoluble, successful solubilization steps were implemented subsequently. Reactivity tests with sera from rabbits immunized with a DNA-RBD vaccine, sera from COVID-19 patients, and pre-pandemic sera showed that all fusion proteins were recognized, although with varying efficiencies. The fusion protein that includes fragments of the E protein at the N-terminal and epitopes of the M protein at the C-terminal fused to the RBD (E-RBD-M) stood out as the most promising. This fusion, along with the RBD, was used in mouse immunization schemes, triggering a robust humoral immune response, with the production of high-avidity antibodies assessed by ELISA. Furthermore, sera generated by both proteins demonstrated the ability to generate neutralizing antibodies, as evidenced by assays inhibiting RBD binding with ACE2. The RBD and the fusion were tested with sera from COVID-19 patients and vaccinated individuals, as well as sera negative for the infection. The E-RBD-M fusion, while sensitive, proved to be less specific compared to the RBD. Cellular immune response was also evaluated by qPCR and ELISA, revealing the induction of high levels of cytokines after immunization and restimulation of splenocytes, suggesting a robust cellular response. These results highlight the potential of RBD fusions as promising candidates for COVID-19 diagnosis and immunization, representing a simple and cost-effective production approach with immunogenicity comparable to the RBD expressed in this study.